PENGARUH JENIS MULSA DAN DOSIS BOKASHI TERHADAP PERTUMBUHAN KACANG PANJANG (Phaseolus vulgaris L) - Ahmad Raksun; Lalu Japa (Jurnal Penelitian Pendidikan IPA, 2019)
Research about the effect of different types of mulch  and dosage of bokashi on the growth of long bean has done in Sukarara village Central Lombok. The purpose of conducting research are  (1) to identify the effect of different types of mulch on the  long bean growth, (2) to identify the effect of bokashi on the long bean growth, (3) to identify the effect of interaction betwen different types of mulch and dosage of bokashi on the long bean growth. In this research, factorial design was used consisting of 2 factors. The first factor is the type of mulch  and the second factor is the dosage of bokashi. The data was analyzed using Anova and least significant differens test (LSD).The result showed that: (1) different types of mulch have no significant effect on the growth of long bean, (2)  bokashi dosage has a significant effect on long bean growth, (3) interaction of mulch types and bokashi dosage did not significantly effect long bean growth Key words: mulch, bokashi, growth, long bean